New Directions Housing Policy of the Republic of Kazakhstan basis of socio-economic development (Journal of Economic Research & Business Administration, 2015)
In the article the housing market is considered as a basis of social and economic development of the country. The rent market is offered to be considered, as the perspective direction of increasing supply of housing.Analyzed the world and foreign experience of functioning of the rent market of housing. It is shown a positive influence of development of rent housing on the general condition of the market of housing in Kazakhstan. Housing programmes and the policy are analyzed, that was accepted since independence and their flaw are revealed. Normative documents and the laws which have influenced development of the market of housing in RK are considered. New approaches to realization of housing policy are considered, stages of implementation of programs and their methodical order are shown. Dynamics of structure and structure of housing stock of the Republic of Kazakhstan over the last ten years is shown. Revealed a number of properties of efficiency of policy of housing.
Keywords: housing; housing market; construction; market rental housing; reform; housing policy